Students' Cooperative Attitudes in Junior High School Mathematics Learning: A Study of the Influence of the Project-Based Learning Model on Integer Material - Sari, Putri Novita; Fitriatien, Sri Rahmawati; Prayitno, Lydia Lia (Plusminus: Jurnal Pendidikan Matematika, 2025)
Rendahnya sikap kerjasama siswa dalam pembelajaran matematika berdasarkan observasi awal menunjukkan perlunya penerapan model pembelajaran yang dapat meningkatkan sikap tersebur. Tujuan studi ini adalah meneliti pengaruh PjBL terhadap sikap kerjasama siswa dalam pembelajaran matematika dengan metode kuantitatif desain quasi eksperimen berupa posttest-only control group design. Populasi penelitian adalah seluruh siswa kelas VII SMP Negeri 20 Surabaya. Dua kelas menjadi sampel penelitian melalui teknik pemilihan purposive sampling. Model PjBL diterapkan di kelas VII-I, sedangkan kelas VII-G menggunakan metode pembelajaran konvensional. Instrumen pengumpulan data berupa lembar observasi untuk menilai sikap kerjasama siswa selama pembelajaran. Data dianalisis menggunakan uji normalitas, uji homogenitas, dan uji-t. Hasil uji hipotesis menunjukkan adanya perbedaan rata-rata sikap kerjasama siswa pada kelas kontrol dan kelas eksperimen, di mana kelas eksperimen menunjukkan hasil yang lebih tinggi. Berdasarkan hasil tersebut, model PjBL berpengaruh positif terhadap sikap kerjasama siswa dalam pembelajaran matematika. Studi ini penting dilakukan karena sikap kerjasama merupakan salah satu keterampilan abad 21 yang perlu dikembangkan dalam pembelajaran matemataika. The low level of students' collaboration skills in mathematics learning, based on initial classroom observations, indicates the need for a learning model that can enhance such skills.  This study aims to examine the effect of PjBL on students' cooperative attitude in learning mathematics using a quantitative quasi-experimental design with a posttest-only control group. The population consisted of all seventh-grade students at SMP Negeri Surabaya. Two classes were selected as the research sample using a purposive sampling technique. The PjBL model was applied in class VII-I, while class VII-G used conventional learning methods. The data collection instrument was an observation sheet used to assess students' cooperative attitude during learning. Data were analyzed using normality tests, homogeneity tests, and t-tests. The results of the hypothesis test showed a significant difference in the average attitude of student cooperation between the control class and the experimental class, with the experimental class yielding higher results. Based on these results, the PjBL model has a positive impact on students’ cooperative attitude in learning mathematics. This study is important because cooperation is one of the 21st-century skills that needs to be developed through mathematics education.